2014
DOI: 10.1063/1.4860016
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic orders of LaTiO3 under epitaxial strain: A first-principles study

Abstract: Perovskite LaTiO 3 bulk is a typical Mott-insulator with G-type antiferromagnetic order. In this work, the biaxial strain effects on the ground magnetic order of LaTiO 3 films grown on various substrates have been studied. For the compressive strain, LaTiO 3 films grown on LaAlO 3 , LaGaO 3 , and SrTiO 3 substrates undergo a phase transition from the original G-type antiferromagnet to A-type antiferromagnet. The underlying physical mechanisms are the lattice distortions tunned by strain. While for the tensile … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 22 publications
2
21
1
Order By: Relevance
“…A 7 × 7 × 5, 5 × 7 × 7 and 7 × 7 × 5 Monkhorst-Pack k-point mesh centered at Γ point are adopted for ( The Hubbard repulsion U eff (= U − J) is imposed on Ti's/V's 3d and La's 4f orbitals using the Dudarev implementation [26]. According to previous literature [27][28][29], U eff (Ti)=2.3 eV, U eff (V)=3 eV, and U eff (La)=8 eV are proper to reproduce the experimental properties and thus are adopted as default parameters in the following calculations, if not noted explicitly.…”
Section: Models and Methodsmentioning
confidence: 99%
“…A 7 × 7 × 5, 5 × 7 × 7 and 7 × 7 × 5 Monkhorst-Pack k-point mesh centered at Γ point are adopted for ( The Hubbard repulsion U eff (= U − J) is imposed on Ti's/V's 3d and La's 4f orbitals using the Dudarev implementation [26]. According to previous literature [27][28][29], U eff (Ti)=2.3 eV, U eff (V)=3 eV, and U eff (La)=8 eV are proper to reproduce the experimental properties and thus are adopted as default parameters in the following calculations, if not noted explicitly.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The optimized equilibrium values for lattice con- Table I, the G-AFM have the lowest energy and the C-AFM is the first excited state with a proximate energy due to the strain effect, similar to the pure LTO film grown on the LSO substrate. 31 The energy difference ∆E and the local magnetic moment M Ti do not change too much when n changes from 2 to 4 for these (001)-oriented SLs. Such a behavior is due to the highly insulating LSO barrier, namely these ultra-thin LSO layers are enough to isolate LTO bilayers.…”
mentioning
confidence: 99%
“…Our previous DFT calculation reported that the LTO film has a tendency to approach the C-AFM under tensile strain from substrates with relative large lattice constants, such as LSO used in the present work. 31 For these SLs, both the lattice constants along the c-axis and inner atomic positions are fully optimized until the Hellman-Feynman forces are less than 10 meV/Å.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…LaScO 3 ) maintain the G-type antiferromagnetism (G-AFM) as in bulk. 8 It is reported that the compressive LaTiO 3 films may even undergo an insulator-to-metal transition. 9,10 Moreover, the strain effects depend on not only the simple lattice constants (e.g.…”
mentioning
confidence: 99%